Carbon nanotubes as carriers of Panax ginseng metabolites and enhancers of ginsenosides Rb1 and Rg1 anti-cancer activity. (28th November 2016) - Lahiani, Mohamed H; Eassa, Souzan; Parnell, Charlette; Nima, Zeid; Ghosh, Anindya; Biris, Alexandru S; Khodakovskaya, Mariya V
Abstract: A major benefit to nanomaterial based-medicine is the ability to provide nanosized vehicles for sporadic metabolites. Here, we describe how the conjugation of valuable ginseng secondary metabolites (ginsenoside Rb1 or Rg1) with carbon nanotubes (CNT) can enhance their anti-proliferative and anti-cancer effects. Ginsenoside-CNT conjugate (Rb-CNT or Rg-CNT) permitted the ginsenosides to be used at a low dose, yet achieve a higher incidence of cancer killing. We were able to demonstrate that the ginsenoside-CNT conjugate can decrease cell viability up to 62% in breast cancer cells (MCF-7) and enhance antiproliferation of drug-resistant pancreatic cancer cells (PANC-1) by 61%. The interaction of the ginsenoside-CNT conjugate with breast cancer cells was studied using Raman Spectroscopy mapping. Total transcriptome profiling (Affymetrix platform) of MCF-7 cells treated with the ginsenoside-CNT conjugate shows that a number of cellular, apoptotic and response to stimulus processes were affected. Therefore, our data confirmed the potential use of CNT as a drug delivery system.